Эффекты квантовой интерференции в дельта-слоях бора в кремнии - Красовицкий, Вит.Б.; Комник, Ю.Ф.; Миронов, М.; Волл, Т.Е. (Физика низких температур, 2000)
Исследовано поведение проводимости при изменении температуры (в интервале 1,5-40 К) и напряженности магнитного поля (до 20 кЭ) для серии образцов с δ⟨Bс)-слоем в Si с концентрацией дырок в проводящем d-слое 2,5×10¹³-2,2×10¹⁴ см⁻² . Показано, что эти зависимости успешно объясняются проявлением эффектов слабой локализации и взаимодействия подвижных носителей заряда (дырок) в двумерной электронной системе в условиях сильного спин-орбитального взаимодействия. Из анализа поведения квантовых поправок определена температурная зависимость времени фазовой релаксации носителей τφ=AT⁻¹ , где A≈(1,4±0,3)×10⁻¹²K⋅c, рассматриваемая как проявление процессов междырочного рассеяния, а также получены значения константы взаимодействия (λT≈ 0,64- 0,73). The behavior of the conductance upon changes in temperature (in the interval 1.5–40 K) and magnetic field (up to 20 kOe) is investigated for a series of samples with a δ〈B〉 layer in Si, with hole concentrations in the conducting δ layer of 2.5×10¹³–2.2×10¹⁴ cm⁻². It is shown that the temperature and field dependences obtained can be explained successfully as a manifestation of the weak localization effect and the interaction of mobile charge carriers (holes) in a two-dimensional electron system under conditions of strong spin–orbit interaction. An analysis of the behavior of the quantum corrections yields the temperature dependence of the phase relaxation time of the carriers, τφ=AT⁻¹, with A≈(1.4±0.3)×10⁻¹² K⋅s, where this temperature dependence is treated as a manifestation of hole–hole scattering processes, and the values of the interaction constants are also obtained (λT≈0.64–0.73).